Compression curved plate loaded with compressive forces applied to unreinforced edges - N.Melikulov; S.K.Kuchkorov; U.Khushvaktov; O.M.Ubaydullaev (Genius Journals, 2022)
In this article, free oscillation of the plate is considered when the sides
Keywords: compressed, compression curved, tensile, plates, elastic pinched, hinged, torsional, bending, reinforced, unreinforced, edge, rigidity